Colorimetric chemosensing of Riboflavin using polymeric micro-array reinforced by silver nanoparticle: State-of-the-art on one-drop biomedical analysis - Farnaz Bahavarnia; Milad Baghal Behyar; Azadeh Nilghaz; Mohammad Hasanzadeh; Nasrin Shadjou (Scientific Reports)
Abstract Riboflavin, vitamin B2, is an essential micronutrient involved in energy metabolism and cellular function, making its monitoring crucial for clinical diagnostics, food quality control, and nutritional research. In this study, a parafilm-based micro-array was fabricated and utilized for colorimetric detection of riboflavin using triangular silver nanoparticles (TA-AgNPs) as an optical probe. The interaction between riboflavin and silver nanoparticles induced changes in the NPs’ localized surface plasmon resonance (LSPR), resulting in a visible color change. This phenomenon was systematically studied by varying riboflavin concentrations and observing the corresponding optical response using UV–Vis spectroscopy. Riboflavin was detected in human plasma samples using CMYK colorimetric integrated digital image analysis by smartphones with a linear detection range of 0.1 to 100 mM and low limit of quantification of 0.1 mM in the standard solution of analyte. Using the unique plasmonic properties of TA-AgNPs and the construction simplicity of parafilm-based micro-array system, we aimed to provide a cost-effective, portable, and efficient method for riboflavin detection. The proposed platform has the potential to develop point-of-care diagnostics and on-site testing by offering a robust alternative to traditional laboratory-based analytical techniques and well plates.